Transition in East Germany: A British view - Vincent Edwards; Peter Lawrence (Journal for East European Management Studies, 1996)
The article reviews the process whereby two British academics (with prior knowledge and experience of both the FRG and GDR) developed in 1990 a research project to investigate how an East German company made the transition from communism to privatisation. The project soon developed from a longitudinal study of one company to encompass a range of companies differentiated by location, industry, privatisation stage and mode, and owner origins. The analysis of the interview data permitted the identification of patterns and commonalties of the emergence of corporate strategy. The authors portray the main characteristics of different phases of that process and indicate that not every company had progressed through all phases of the process. – – Der Artikel beschreibt die Ergebnisse von zwei britischen Wissenschaftlern (mit Vorkenntnissen und Erfahrungen sowohl zur BRD als auch zur DDR) aus einem Projekt, das 1990 begonnen wurde, um den Übergang eines Unternehmens vom Kommunismus zur Privatisierung zu erforschen. Das Projekt wurde bald von einer Längsschnittstudie eines Unternehmens durch Einbeziehung weiterer Firmen verschiedener geographischer Lage, Industriezweige, Privatisierungsstadien und -wege und Herkunft der Eigentümer erweitert. Die Analyse der Interviewdaten erlaubt die Identifizierung von Mustern und Gemeinsamkeiten des Entstehens der Unternehmensstrategie. Die Verfasser beschreiben die Hauptmerkmale der verschiedenen Phasen dieses Prozesses und zeigen auf, daß nicht jede Firma bisher alle Phasen bewältigt hat.
Keywords: 650